2020
DOI: 10.3390/ijms21217878
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Kinase Domain of MerTK in Complex with AZD7762 Provides Clues for Structure-Based Drug Development

Abstract: Aberrant tyrosine-protein kinase Mer (MerTK) expression triggers prosurvival signaling and contributes to cell survival, invasive motility, and chemoresistance in many kinds of cancers. In addition, recent reports suggested that MerTK could be a primary target for abnormal platelet aggregation. Consequently, MerTK inhibitors may promote cancer cell death, sensitize cells to chemotherapy, and act as new antiplatelet agents. We screened an inhouse chemical library to discover novel small-molecule MerTK inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Previously, a thermal shift assay using purified MERTK kinase domains in an in-house kinase-inhibitor library revealed that 8 of 356 compounds exhibited a melting temperature shift of >1 °C 15 . Among them, BMS794833 (IUPAC name; N -[4-(2-amino-3-chloropyridin-4-yl)oxy-3-fluorophenyl]-5-(4-fluorophenyl)-4-oxo-1 H -pyridine-3-carboxamide; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, a thermal shift assay using purified MERTK kinase domains in an in-house kinase-inhibitor library revealed that 8 of 356 compounds exhibited a melting temperature shift of >1 °C 15 . Among them, BMS794833 (IUPAC name; N -[4-(2-amino-3-chloropyridin-4-yl)oxy-3-fluorophenyl]-5-(4-fluorophenyl)-4-oxo-1 H -pyridine-3-carboxamide; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whole cloning and purification protocols followed a previous report 15 . In a biochemical activity assay, the gene coding the N-terminal His 6 tag-thrombin-MERTK kinase domain (residues 571–864, wild type; WT) was subcloned into the pETDuet-1-PTPN1 (pETDuet-1 vector containing the PTPN1 (1–330) gene at MCS2, Merck Millipore, USA) bacterial expression vector using the Nco1 and Not1 cloning sites at MCS1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Recent advances in kinase drug discovery span the drug discovery pipeline from target identification through to pharmacovigilance. These advances are illustrated in six primary research articles covering kinome array profiling [ 4 ], structure-guided drug development [ 5 , 6 ], rational computational design [ 7 ], targeting the protein/peptide substrate binding site [ 8 ] and combinatorial drug treatment [ 9 ]; and nine topical reviews on TAO kinases [ 10 ], liver disease [ 11 ], AMPK [ 3 ], pancreatic cancer [ 12 ], urothelial carcinoma [ 13 ], Flaviviridae infections [ 14 ], squamous cell carcinoma [ 15 ], thyroid cancer [ 16 ] and adverse reactions to JAK inhibitors [ 17 ]. The indicated figures from special issue papers have been re-used with permission from the authors.…”
mentioning
confidence: 99%
“…Park et al [ 5 ] report the crystal structure of the emerging target, tyrosine protein kinase Mer (MerTK), in complex with a Checkpoint (Chk) kinase inhibitor, AZD7762. Interestingly, the structural data and impact of AZD7762 on the auto-phosphorylation of MerTK in two lung cancer cell lines suggest that AZD7762 targets a partially inactive state of the kinase.…”
mentioning
confidence: 99%